Enzymatic hydrolysis of corn crop residues with high solid loadings: New insights into the impact of bioextrusion on biomass deconstruction using carbohydrate-binding modules. (June 2019) - Gatt, Etienne; Khatri, Vinay; Bley, Julien; Barnabé, Simon; Vandenbossche, Virginie; Beauregard, Marc
Highlights: Bioextrusion improved enzymatic hydrolysis efficiency of raw corn crop residues. FTCM assisted to study the surface cellulose accessibility profile. Negative impact of high S/L ratio was not due to the lack of exposed cellulose. Alkaline pretreatment strongly limits bioextrusion's positive influence. Abstract: Lignocellulosic biomass is a sustainable source of renewable substrate to produce low carbon footprint energy and materials. Biomass conversion is usually performed in two steps: a biomass pretreatment for improving cellulose accessibility followed by enzymatic hydrolysis of cellulose. In this study we investigated the efficiency of a bioextrusion pretreatment (extrusion in the presence of cellulase enzyme) for production of reducing sugars from corn crop agricultural residues. Our results demonstrate that bioextrusion increased the reducing sugar conversion yield by at least 94% at high solid/liquid ratio (14%–40%). Monitoring biomass surface with carbohydrate-binding modules (FTCM-depletion assay) revealed that well known negative impact of high solid/liquid ratio on conversion yield is not due to the lack of exposed cellulose which was abundant under such conditions. Bioextrusion was found to be less efficient on alkaline pretreated biomass but being a mild and solvent limiting pretreatment, it might help to minimize the waste stream.